PROJECT-BASED LEARNING FOR DEVELOPING INTEGRATED SKILLS IN A2 LEARNERS - Fakhrullo Madaminov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Project-based learning (PBL) has been promoted as an instructional approach that fosters meaningful learning, collaboration, and integration of multiple language skills. This paper investigates how PBL can be designed and implemented specifically  to  develop  integrated  skills  (listening,  speaking,  reading,  writing)  in English  learners  at  the  CEFR  A2  level.  Using  a  systematic  review  and  thematic synthesis of empirical and theoretical literature (2000–2024), the study summarizes PBL  principles,  examines  evidence  of  effectiveness  for  language  learning,  and identifies  design  features  and  assessment  strategies  that  optimize  learning  for  A2 pupils.  Findings  indicate  that  well-scaffolded  PBL  units—characterized  by  clear driving questions, staged scaffolding, multimodal tasks, explicit language focus, and formative  assessment—support  integrated  skill  growth  and  learner  motivation. However, the strength of the evidence base for A2-specific outcomes remains emerging and uneven: many studies report positive attitudinal and communicative gains, while robust long-term, CEFR-aligned outcome data are limited. The paper concludes with practical  unit  designs  tailored  to  A2  classrooms,  recommended  teacher  roles, assessment rubrics, and directions for longitudinal and controlled research.